Sequestration Security in A Remote Sensor Network - Anand, Niketha; Amaran, Sibi; R.S. , Preyanka Lakshme (International Journal of Psychosocial Rehabilitation, 2020)
The implementation of identifying a malicious node in a system and then removing the malicious nodes detected to prevent errors that might occur due to them. An effective security program is one that does not have any malicious nodes. Few techniques, such as viruses, spyware, and Trojan horses. Message authentication and checksum are involved in the implementation of identifying malicious nodes. The tools used are Network Simulator 2, cryptography, and the GSTEB algorithm. Network Simulator is an open-source program designed specifically for research in computer communication networks. The proposed work can solve sequestration security in a network and detect any intruder detections on a cluster of data in a network; it not only detects attacks but also handles them.